The Efforts to Completion of Contract Restructuring Due to Covid-19 - Ismi, Nur; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This study aims to identify and analyze the form of settlement by the BankonFinancing Facility Due to COVID-19; To find out and analyze the Recruitment Contract Settlement Technique for the Impact of Covid-19; as well as to find out and analyze the Obstacles and Solutions to Settlement of Restructuring Contracts Impact of COVID-19.The type of research used is empirical normative research. The research uses qualitative analysis, which is a method of research that produces descriptive analytical data, which are stated by respondents in writing or verbally as well as real behavior, which is researched and studied as a whole. Primary data is data obtained from practices that occur and secondary data is carried out by means of tertiary legal material literature research. Collecting data in this study by means of observation and interviews. Based on the research it was concluded that ppotential customers unable to pay onBankdue to impactthe spread of COVID-19, but this impact has been anticipated by the Regulation of the Financial Services Authority of the Republic of Indonesia Number 11/POJK.03/2020 concerning National Economic Stimulus as a Countercyclical Policy on the Impact of the Spread of Coronavirus Disease 2019 (COVID-19), where POJK provides an opportunity to restructure financing by taking into account the criteria that the specified customers are customers affected by the spread of COVID-19 and paying attention to the sectors affected by the spread of COVID-19.Completion of Impact Restructuring AgreementCOVID-19as follows: Rescheduling; Reconditioning; and Restructuring. Basically, there are 2 constraints that occur in the settlement of troubled financing at the Bank, namely First, Delays in customers completing administrative requirements for online verification. Second, the obstacle in verifying document requirements is when a customer is dishonest in reporting economic conditions after being affected by a virus outbreakCOVID-19. Keywords: Bank; Contract; Restructuring.